Chemical Melting of Ice: Effect of Solution Freezing Point on the Melting Rate. Issue 1 (2016) - Wåhlin, Johan; Klein-Paste, Alex
Icy roads in wintertime present a hazard for road users. It is therefore desirable to maintain bare roads. To achieve this, deicing chemicals are typically applied. One important property of the chemicals that are used is how fast they can melt ice. Understanding what affects the melting rate, however, is limited. An experiment was therefore designed to study how the driving force for the melting—the chemical potential difference between ice and solution—affects the chemical melting rate of ice. In this study, the driving force was represented by the solution freezing points. The experiment was performed at −5°C (23°F) by using the solutions of four chemicals: sodium chloride, magnesium chloride, and calcium chloride, as well as potassium formate. These four solutions were mixed to have four freezing points. They were −10°C (14°F), −18°C (−0.4°F), −30°C (−22°F); and the eutectic temperature of each chemical. The results showed that there was a clear correlation between solution freezing point and how fast the solution could melt ice. The solutions with the lowest freezing point melted ice four to five times faster than the solutions with the highest freezing point. The importance of solution freezing point was attributed to its direct relation to the solution chemical potential, with a low freezing point giving a large driving force for the phase change. In addition, it was found that the type of chemical plays a role on the melting rate of ice. The fastest melting chemical (potassium formate) melted ice 45% faster than the slowest melting chemical (magnesium chloride), which is attributed to potassium formate having a higher ion mobility. A higher ion mobility allows a faster transport of solute to the ice–solution interface.